Managing recidivism risks within the parole system / Zaiton Hamin, Mohd Bahrin Othman and Rafizah Abu Hassan - Hamin, Zaiton; Othman, Mohd Bahrin; Abu Hassan, Rafizah (2014)
The parole system is responsible for rehabilitating prisoners and assisting them in their reintegration into the society successfully. This undertaking aims in protecting public safety and reducing recidivism or reoffending amongst the prisoners released on parole. However, the implementation of the system without any empirically informed strategies and practices will generate higher costs in the future, as the risks and the cycle of recidivism continues. This paper aims at examining the manner in which parole agencies manage the risks of recidivism and the risks to public safety within the constraints of their available human and financial resources. In particular, the paper will focus on the supervision strategy and practices as well as the challenges confronting the parole officers in dealing with the risk of reoffending by the prisoners. This conceptual paper employs a doctrinal approach in which secondary data comprising of the primary source involving the Prison Act 1995 and secondary sources including articles in academic journals, books, online database and Internet sources are analysed. This paper contends that managing the recidivism risks involved in the parole system is problematic, requiring not only internal and external support, but also the adoption of viable strategies such as risk targeting, evidence-based program and continuum care approach in a comprehensive manner.